Lead determination at ng/mL level by flame atomic absorption spectrometry using a tantalum coated slotted quartz tube atom trap - Demirtas, Ilknur; Bakirdere, Sezgin; Ataman, O. Yavuz (ELSEVIER, 2015)
Flame atomic absorption spectrometry (FAAS) still keeps its importance despite the relatively low sensitivity; because it is a simple and economical technique for determination of metals. In recent years, atom traps have been developed to increase the sensitivity of FAAS. Although the detection limit of FAAS is only at the level of mu g/mL, with the use of atom traps it can reach to ng/mL. Slotted quartz tube (SQT) is one of the atom traps used to improve sensitivity. In atom trapping mode of SQT, analyte is trapped online in SQT for few minutes using ordinary sample aspiration, followed by the introduction of a small volume of organic solvent to effect the revolatilization and atomization of analyte species resulting in a transient signal. This system is economical, commercially available and easy to use. In this study, a sensitive analytical method was developed for the determination of lead with the help of SQT atom trapping flame atomization (SQT-AT-FAAS). 574 Fold sensitivity enhancement was obtained at a sample suction rate of 3.9 mL/min for 5.0 min trapping period with respect to FAAS. Organic solvent was selected as 40 mu L of methyl isobutyl ketone (MIBK). To obtain a further sensitivity enhancement inner surface of SQT was coated with several transition metals. The best sensitivity enhancement, 1650 fold enhancement, was obtained by the Ta-coated SQT-AT-FAAS. In addition, chemical nature of Pb species trapped on quartz and Ta surface, and the chemical nature of Ta on quartz surface were investigated by X-ray photoelectron spectroscopy (XPS) and Raman Spectroscopy. Raman spectrometric results indicate that tantalum is coated on SQT surface in the form of Ta2O5. XPS studies revealed that the oxidation state of Pb in species trapped on both bare and Ta coated SQT surfaces is +2. For the accuracy check, the analyses of standard reference material were performed by use of SCP SCIENCE EnvirolVIAT Low (EU-L-2) and results for Pb were to be in good agreement with the certified value using SQT-AT-FAAS and Ta coated-SQT. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Flame atomic absorption spectrometry; Slotted quartz tube; Lead; Tantalum; Preconcentration; Atom trapping; CADMIUM; SILICA; COPPER; GENERATION; ANTIMONY; PLANTS; XPS; Chemistry